Implementation of Undika Futuristic Learning Model (Ufl) in Islamic Education Course - Muvid, Muhamad Basyrul (Maharot : Journal of Islamic Education, 2024)
Hybrid learning in this digital era is seen as an alternative in creating a flexible and enjoyable learning atmosphere, but there is no learning model that explains the steps (syntax) of hybrid learning which will later affect the selection of strategies, methods and assessment aspects. One of the hybrids learning models is UFL (Undika Futuristic Learning) which has a specific syntax so it is hoped that the implementation of hybrid learning can be clearly directed. The purpose of this study is to describe the implementation of the UFL model in Islamic religious education courses at Dinamika University of Surabaya. The research method in this article uses a case study, with analysis techniques and systematic compilation of findings. The results of this study indicate that the UFL learning model based on hybrid with PBL strategy and case-based learning method supported by UFL syntax in Islamic religious education courses gives a positive impression and impact on the cognitive, affective and psychomotor development of students, so that in terms of knowledge they can think critically and innovatively. Affectively they can work together, be responsible, learn independently and be confident. And psychomotorically they can think creatively and are skilled in compiling and delivering their solutions optimally. In this context, learning with the UFL model in theory and fact can cover the three domains, so that learning objectives can be achieved according to the needs of the current era which emphasizes problem-solving skills so that they are able to think critically, creatively and innovatively within a collaborative framework.